Feedback and cooperation: An Experiment in sorting behavior - Berlin, Noémi; Gueye, Mamadou; Monjon, Stéphanie (Ecological economics, 2025)
In this paper, we use a laboratory experiment to analyze the effect of information provision (feedback) on individual sorting behavior. Effective sorting requires both quantity and quality, yet increasing quantity may reduce quality due to the higher risk of contamination. We conduct a collective sorting behavior experiment consisting of a two-stage coordination game in which two subjects are paired and then individually decide whether or not to participate in a collective sorting task. The performance achieved depends on the quantity and quality of sorting, and the payoff depends on the decision and performance of both subjects in the task. Information about the subject’s own past performance, and information about the partner’s past performance, are included as feedback treatments. Using a between-subjects experimental design, we find that the feedback type has very different effects on participation, performance and coordination (defined as both subjects succeeding in the sorting task). Only feedback about one’s own performance leads to better performance and more coordination. Although this experiment is not contextualized, the results provide useful pointers for waste sorting policies. •The experiment mimics, in a context-free setting, waste sorting behaviour.•It is represented by a coordination game.•Our experiment studies coordination of individuals in a collective sorting task.•Quantity and quality levels are interlinked and determine the success in the task.•We test how providing information affects participation and success in coordination.•Sharing a partner’s past performance tends to discourage participation.•Sharing one’s own performance data increases both performance and coordination.